Budget Efficiency and Effectiveness as Drivers of Financial Performance: Evidence from a Wood-Processing SME in Indonesia - Yayu Rakkang; Fahruni Khaerunnisa (Liquidity Jurnal Ilmu Manajemen dan Bisnis, 2026)
Budgeting serves as a critical instrument for planning, control, and performance management, particularly in manufacturing firms that operate under volatile market conditions. This study aims to analyze the efficiency and effectiveness of budgeting practices at PT. Jian Jaya Perkasa, a wood-processing company, in order to understand how budgeting contributes to financial sustainability and organizational performance. Employing a descriptive qualitative design, the research combined semi-structured interviews, direct observations, and document analysis, supported by quantitative ratio calculations of effectiveness and efficiency. The findings reveal that the company improved its budget effectiveness from 91 percent in 2022 to 104 percent in 2023, exceeding its revenue targets. Simultaneously, budget efficiency improved from 96 percent to 80 percent, reflecting stronger cost control and resource optimization. Qualitative insights highlighted that these improvements were driven by tighter expenditure monitoring, refined revenue forecasting, and enhanced inter-departmental coordination. Nevertheless, challenges such as raw material price volatility and delays in budget realization continued to exert pressure on financial outcomes. The company’s adaptive strategies—including supplier diversification, adjustments to service lines, and improved communication—proved critical in mitigating these constraints. The study concludes that robust and adaptive budgeting practices significantly enhance financial performance by linking strategic alignment with operational effectiveness. These results contribute to the growing body of knowledge on budgeting by demonstrating the interplay of efficiency and effectiveness in sustaining organizational resilience, while also offering practical lessons for small and medium-sized enterprises facing resource constraints.